STUDY OF MECHANISMS OF LIGHT ABSORPTION IN TITANIUM DIOXIDE FILMS - V. V. Novopashin; L. A. Skvortsov; M. I. Skvortsova (Тонкие химические технологии)
This work is devoted to comparison of optical absorption value of titanium dioxide coatings obtained by means of reactive thermal evaporation (RTE) and its activated species (ARTE), as well as to study on the dependence of the absorption coefficient of the coatings on the process parameters. Special attention is paid to the study of the influence of the films nonstoichiometry on absorption in the visible and near-infrared ranges of the spectrum. The results allow concluding that the dominant mechanism responsible for absorption in titanium dioxide films in the near-infrared range of the spectrum is the deviation from the stoichiometric composition. This deviation is caused by the presence of defects in the coating structure such as oxygen vacancies (ions Ti3+), which are seen as electron traps. As oxygen pressure and ionic current increase, the absorption of titanium dioxide films is reduced, and films with a composition closer to stoichiometric are obtained. In turn, the absorption of titanium dioxide in the visible spectrum (at wavelengths of 532 nm and 670 nm) has less to do with defects in stoichiometry, in contrast to contaminating impurities contained in the starting material, in the vacuum chamber and in the jet gas.